GLOBAL EXPERIENCE IN IMPROVING THE ORGANIZATION AND MANAGEMENT OF SMALL INDUSTRIAL ZONES AND THE INTRODUCTION OF A WIN-WIN SYSTEM (NO LOSERS) TO DIRECTORATE OF THE SIZ OF THE KHAREZM REGION - Akhmedov Zafar Kadirovich (Scholar Express Journals, 2025)
This study focuses on the improvement of the system of formation and management of small industrial zones in the Kharezm region of Republik of Uzbekistan. The purpose of the research is to identify the current state of small industrial zones in the region, analyze the existing system of their formation and management, and propose recommendations for its improvement. The study employs qualitative research methods, including document analysis and interviews with key stakeholders. The findings reveal that the current system of formation and management of small industrial zones in the Kharezm region faces several challenges, including inadequate infrastructure, lack of financing, and insufficient support from local authorities. The study proposes a range of recommendations to address these challenges, such as improving infrastructure, providing financial support, and enhancing the involvement of local authorities in the formation and management of small industrial zones. The study contributes to the literature on industrial zones and provides practical insights for policymakers and practitioners in the field.
Keywords: small industrial zone; taxes; privileges; effective management